Pengaruh Modal Intelektual terhadap Kinerja Organisasional: Studi pada Konteks Perguruan Tinggi di Indonesia - Sofyani, Hafiez; Khairunisa, Aulia (E-Jurnal Akuntansi; Vol 31 No 7 (2021), 2021)
This study examined the effect of intellectual capital on the performance of higher education institutions (HEIs) in Indonesia. This research was conducted using a questionnaire survey approach. The sample of this research was HEIs in Java island, while the research respondents are structural officials. The relationship between the intellectual capital and HEI performance was tested using the regression analysis. This study found empirically that intellectual capital has a positive effect on the performance of HEIs. In detail, it was found that structural and relational capital positively influence HEI performance whilst human and social capital do not. From these findings, it is suggested that efforts to manage intellectual capital in HEIs should continue to be improved, i.e. structural and relational capital dimensions in particular, given the positive impact these two bring. Keywords: Intellectual Capital; Higher Education Institutions; Performance.